MUSIC IN TIMES OF CHANGE - A REFLECTION ABOUT ITS ROLE IN EDUCATION - Marisa Trench de O. Fonterrada (Editora da Universidade de Santa Cruz do Sul, 2014)
In this paper I discuss the new conditions of the teachers who teach basic education in the first years of school - children from 4 to 11 years old - after the enactment of Law No. 11.769/2008, which requires the inclusion of music in the school curriculum. With the purpose of supporting this discussion, a review of significant changes that occurred in the world, especially in the nineteenth and twentieth centuries until the present days, was conducted. These changes contain patterns of the Modernity and Post-Modernity and deeply affect the manner of conceiving education, specifically music education. From this discussion emerges a new posture about music highlighting its role nowadays, different from the exclusive understanding of music as entertainment or leisure. Instead, music is now conceived as responsible for human development and instigator of autonomy and freedom. Some possible manners of using music in the classrooms, through singing plays and games, and as an aid to other subjects of the curriculum are also suggested. This paper ends inviting teachers to receive music in their own lives and share it with their students.